Olive Knot Pathogen with Pronounced Epiphytic Lifestyle is not Present in Association to Leaf Surface of European Olive Across the Himalayas in Nepal. Issue 3 (2nd September 2013) - Lamichhane, Jay Ram; Varvaro, Leonardo
Abstract Pseudomonas savastanoi pv. savastanoi, the causal agent of olive knot disease, often switches from a saprophytic to a parasitic lifestyle only following natural or man‐made activities, that cause lesions on plant tissues. We investigated the possible presence of this pathogen on the phylloplane of 28 Italian olive cultivars, recently introduced to Nepal. Although a consistent number of bacterial species were found in association with leaf, there was no presence of olive knot pathogen across the study area. The results suggest that the introduction of a new plant species in a given area does not necessarily introduce the pathogen when the propagation materials are rigorously supervised for pathogen exclusion.